2021
DOI: 10.11591/ijere.v10i2.21274
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment in the translation classroom: Closing a feedback loop

Abstract: <span lang="EN-US">Feedback as the key component of formative assessment was studied extensively in the context of the acquisition of the foreign language productive skills by different categories of learners. Similarly, this paper aimed at the investigation of the optimal design of the feedback loop in teaching translation to undergraduate students. A mixed-methods research involved 40 sophomores of Poltava University of Economics and Trade and was conducted during 2018–2019 academic year. It examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The findings of the study showed that most IPT and IEF students indicated agreement with Unfortunately, taking tests online was attractive for some students because of the opportunity to cheat and get more points (Chugai, 2021, p. 111). These results differ from those provided by another study when students of a Spanish university did not indicate any changes resulting in improvement or worsening related to learning online (Erdmann et.al., 2021, p. 33) importance for motivating and encouraging them to take an active position, to be responsible for their progress (Nikolaeva, Korol, 2021). At the same time, some students were aware of the possibility to cheat when taking tests online.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the study showed that most IPT and IEF students indicated agreement with Unfortunately, taking tests online was attractive for some students because of the opportunity to cheat and get more points (Chugai, 2021, p. 111). These results differ from those provided by another study when students of a Spanish university did not indicate any changes resulting in improvement or worsening related to learning online (Erdmann et.al., 2021, p. 33) importance for motivating and encouraging them to take an active position, to be responsible for their progress (Nikolaeva, Korol, 2021). At the same time, some students were aware of the possibility to cheat when taking tests online.…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of pedagogy and psychology, another problem arises when students lack communication skills and motivation. According to previous research (Kiraly, 2000;Nikolaeva and Korol, 2021;Prieto and Linares, 2010;Williams and Williams, 2011), motivation is the most important factor that helps improve learning, and formative assessment in the translation classroom showed that increasing motivation and participation among students enhanced their competence and performance. In translation classrooms, introverted students not only lack communication and social skills but also cultural knowledge because of their lack of participation in class discussions.…”
Section: Problem Statementmentioning
confidence: 98%
“…Based on the results of a survey of science teachers in Bali, 88.9% of teachers have carried out knowledge assessments in formative and summative forms, however, based on the results of interviews, it is known that teachers tend to feel that knowledge assessment in formative form is considered more useful. Providing feedback in formative assessment is key in student learning outcomes (Nikolaeva & Korol, 2021), formative assessment is further learned can improve students' inquiry skills (Ganajová et al, 2021).…”
Section: Assessment Of Knowledge On Indonesian Curriculummentioning
confidence: 99%